Bacterial degradation of pyrene: Biochemical reactions and mechanisms. (August 2021) - Zada, Sahib; Zhou, Haixin; Xie, Jianmin; Hu, Zhong; Ali, Sardar; Sajjad, Wasim; Wang, Hui
Abstract: Pyrene is a typical high molecular weight polycyclic aromatic hydrocarbon (HMW-PAH), and its biodegradation has been widely studied. Different microorganisms, including fungi, bacteria and cyanobacteria, have been shown to degrade pyrene as a source of carbon and energy. Bacteria are important pyrene degraders in different environments. To date, different bacterial phylotypes and their pyrene degradation pathways have been studied. This review will provide the latest information to deepen our understanding of pyrene degradation by bacteria, especially in PAHs contaminated environments. The principal biomarkers of pyrene metabolism ( nidA/B, pah, and phd genes), bacterial community with pyrene degradation ability and their biodegradation mechanisms were reviewed. Additionally, a potential novel pyrene catabolic pathway of Roseobacter clade bacteria was discussed. We suggest that future studies should explore more application of multi-omics approaches and bioinformatics data to identify novel PAHs catabolic enzymes and pathways in other bacteria, rather than limiting research focus in functional genetic indices. Highlights: Different bacteria involved in pyrene degrading were summarized. Degrading mechanism in both aerobic and anaerobic conditions were analyzed. Potential pathway of pyrene catabolism by Roseobacter was discussed.